2011
DOI: 10.1016/j.jalz.2010.08.228
|View full text |Cite
|
Sign up to set email alerts
|

Intracranial atherosclerosis as a contributing factor to Alzheimer's disease dementia

Abstract: Background A substantial body of evidence amassed from epidemiologic, correlative and experimental studies strongly associates atherosclerotic vascular disease (AVD) with Alzheimer's disease (AD). Depending on the precise interrelationship between AVD and AD, systematic application of interventions to maintain vascular health and function as a component of standard AD therapy offers the prospect of mitigating what is presently the inexorable course of dementia. To assess this hypothesis it is vital to rigorous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
89
2
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(97 citation statements)
references
References 64 publications
4
89
2
1
Order By: Relevance
“…Furthermore, an epidemiological study has reported an association between Alzheimer’s disease and some vascular risk factors, including hyperlipidemia 19. Therefore, hyperlipidemia-induced intracranial vascular dysfunction may be a contributing factor to cognitive deficits 20. Our results indicated that TAC also attenuated the increased levels of NEFA, TC, TG, and ApoB in type 2 diabetic rats.…”
Section: Discussionsupporting
confidence: 51%
“…Furthermore, an epidemiological study has reported an association between Alzheimer’s disease and some vascular risk factors, including hyperlipidemia 19. Therefore, hyperlipidemia-induced intracranial vascular dysfunction may be a contributing factor to cognitive deficits 20. Our results indicated that TAC also attenuated the increased levels of NEFA, TC, TG, and ApoB in type 2 diabetic rats.…”
Section: Discussionsupporting
confidence: 51%
“…Substantial evidence from in vitro and biopsy studies also supports the hypothesis that chronic cerebral hypoperfusion plays an important role in the development of AD [7,72,75,[157][158][159]. Hypoperfusion-induced hypoxia evokes vascular responses, in which endothelial cells in the cerebral microcirculation play a central role.…”
Section: Endothelial Response To Chronic Hypoperfusion-related Hypoximentioning
confidence: 76%
“…Few longitudinal studies followed to autopsy support the thesis that hypoxia or oligaemia increases accumulation of AD pathological changes and cognitive dysfunction. Roher and colleagues [55][56][57] have shown that atherosclerotic occlusion of the circle of Willis arteries was more extensive in the AD subjects accompanied by a greater burden of neurofibrillary pathology and white matter rarefaction than in the non-demented ageing individuals but not against subjects with VaD. These observations were not necessarily influenced by the presence of an APOE ε4 allele, however.…”
Section: Vascular Basis Of the Neurovascular Unitmentioning
confidence: 99%